Map and shapefile of the biogeographic provinces of Argentina - Arana, Marcelo D.; Martínez, Gonzalo A.; Oggero, Antonia J.; Natale, Evangelina S.; Morrone, Juan J. (Zootaxa, 2017)
We provide a map of the 15 biogeographic provinces of Argentina based on the ecoregions recognized for the country, combining climatic, geological and biotic criteria. Argentinean provinces belong to the Neotropical region (Yungas, Paraná Forest, Araucaria Forest, Chaco and Pampean provinces), the South American transition zone (Puna, Monte, Comechingones and Cuyan High Andean provinces) and the Andean region (Patagonian, Maule, Valdivian Forest, Magellanic Forest, Falkland Islands and Magellanic Moorland provinces). In order to facilitate future biogeographic analyses, we provide a file of this biogeographical regionalisation in vector format using the World Geodetic Survey 1984.